Higher BMI is associated with higher expiratory airflow normalised for lung volume (FEF25–75/FVC) in COPD. Issue 1 (13th October 2017) - Abston, Eric; Comellas, Alejandro; Reed, Robert Michael; Kim, Victor; Wise, Robert A; Brower, Roy; Fortis, Spyridon; Beichel, Reinhard; Bhatt, Surya; Zabner, Joseph; Newell, John; Hoffman, Eric A; et al.
Abstract : Introduction: The obesity paradox in chronic obstructive pulmonary disease (COPD), whereby patients with higher body mass index (BMI) fare better, is poorly understood. Higher BMIs are associated with lower lung volumes and greater lung elastic recoil, a key determinant of expiratory airflow. The forced expiratory flow (25–75) (FEF25–75 )/forced vital capacity (FVC) ratio reflects effort-independent expiratory airflow in the context of lung volume and could be modulated by BMI. Methods: We analysed data from the COPDGene study, an observational study of 10 192 subjects, with at least a 10 pack-year smoking history. Data were limited to subjects with BMI 20–40 kg/m 2 (n=9222). Subjects were stratified according to forced expiratory volume in 1 s (FEV1 ) (%predicted)-quintiles. In regression analyses and Cox proportional hazard models, we analysed the association between BMI, the FEF25–75 /FVC ratio, the imaging phenotype, COPD exacerbations, hospitalisations and death. Results: There was no correlation between BMI and FEV1 (%predicted). However, a higher BMI is correlated with a higher FEF25–75 /FVC ratio. In CT scans, a higher BMI was associated with less emphysema and less air trapping. In risk-adjusted models, the quintile with the highest FEF25–75 /FVC ratio was associated with a 46% lower risk of COPD exacerbations (OR 0.54, p<0.001) and a 40% lower risk of death (HR 0.60, p=0.02), compared with the lowest quintile. BMI was not independently associated with these outcomes. Conclusions: A higher BMI is associated with lower lung volumes and higher expiratory airflows when normalised for lung volume, as quantified by the FEF25–75 /FVC ratio. A higher FEF25–75 /FVC ratio is associated with a lower risk of COPD exacerbations and death and might quantify functional aspects of the paradoxical effect of higher BMIs on COPD.